1974
DOI: 10.1042/bj1430751
|View full text |Cite
|
Sign up to set email alerts
|

The β-galactosidase-catalysed hydrolyses of β-d-galactopyranosyl pyridinium salts. Rate-limiting generation of an enzyme-bound galactopyranosyl cation in a process dependent only on aglycone acidity

Abstract: 1. beta-d-Galactopyranosyl pyridinium salts are well-behaved substrates for the beta-galactosidase of Escherichia coli, catalysis occurring by the interaction of the salt itself with the normal active site of the protein. 2. logk(cat.) values for seven such salts show a linear relationship (correlation coefficient=-0.997) with the pK(a) of the parent pyridine. 3. The beta-d-galactopyranosyl derivatives of pyridine and 4-bromoisoquinoline exhibit alpha-deuterium kinetic isotope effects of 1.136+/-0.040 and 1.18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

1978
1978
2012
2012

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(27 citation statements)
references
References 35 publications
2
25
0
Order By: Relevance
“…The AAG$ value for the lacZ enzyme, though, is greater than for any of the ebg enzymes, indicating that it has a larger transition-state charge development. This is in accord with higher a-deuterium kinetic isotope effects, both for the formation of galactosyl-enzyme intermediates from galactosyl pyridinium salts [21,26] and for the hydrolysis of the galactosylenzyme intermediates [9,22,23] for the lacZ enzyme than for ebg enzymes. The estimate of charge development from AAG$ for the lacZ enzyme is, moreover, probably an underestimate, since noncovalent events may govern kcat./Km for the monofluoride as they do for other good, uncharged substrates [18,27].…”
Section: Resultssupporting
confidence: 74%
“…The AAG$ value for the lacZ enzyme, though, is greater than for any of the ebg enzymes, indicating that it has a larger transition-state charge development. This is in accord with higher a-deuterium kinetic isotope effects, both for the formation of galactosyl-enzyme intermediates from galactosyl pyridinium salts [21,26] and for the hydrolysis of the galactosylenzyme intermediates [9,22,23] for the lacZ enzyme than for ebg enzymes. The estimate of charge development from AAG$ for the lacZ enzyme is, moreover, probably an underestimate, since noncovalent events may govern kcat./Km for the monofluoride as they do for other good, uncharged substrates [18,27].…”
Section: Resultssupporting
confidence: 74%
“…Before the studies mentioned here, kinetic findings 20,76,91,92 had also suggested that a covalent intermediate exists.…”
Section: Covalent Intermediatementioning
confidence: 71%
“…Specificity b-Galactosidase catalyzes reactions with b-D-galactopyranosides with an oxygen glycosidic bond. 18,19 The enzyme also reacts with substrates having other glycosidic linkages, including nitrogen, 20 sulfur and fluorine, but with much reduced catalytic efficiency. 21 The enzyme is very specific for D-galactose 22-24 and the 2, 3, and 4 positions are especially important.…”
Section: Activity Of Individual B-galactosidase Moleculesmentioning
confidence: 99%
“…The increase in isotope effect from 1.24 to 1.35 for In a subsequent study of fl-D-galactopyranosyl pyridinium salt hydrolysis, the observed linear relationship between V,,,,, and the pK. of the parent pyridine, together with a-deuterium isotope effects of 1.14 and 1.19 for the pyridine and 4-bromoisoquinoline derivatives, led Sinnott and Withers to conclude a rate-limiting formation of a galactosyl carbonium ion for the entire series of substrates (171). I t was suggested that the failure to see a ratedetermining enzyme isomerization for any of these substrates, which are positively charged and do not require general acid catalysis to the departing group, might be due to an association between a protein conformation change and the correct placement of a general acid catalytic group in the hydrolysis of aryl 8-D-galactopyranosides.…”
Section: -Galactosidasementioning
confidence: 99%